Interprofessional training for student conference interpreters and students of political science through joint mock conferences: an assessment. Issue 1 (2nd January 2022) - Defrancq, Bart; Delputte, Sarah; Baudewijn, Tom
ABSTRACT: Interprofessional training is not uncommon in interpreting programmes but seems to be mainly practised in dialogue interpreting. This study reports on an interprofessional training session for conference interpreters and students of political science. A six-hour joint mock conference is annually organised at Ghent University by international students of political science andinterpreted by students of conference interpreting. After one such conference, questionnaires were administered to both groups to gauge experiences, quality perception and learning outcomes for conference interpreters. Findings revealed that students of conference interpreting appreciated the moderately student-centred approach and assessed the learning outcomes very positively, especially because the students of political science challenged their skills. Students of political science assessed the quality of interpretation positively. Relay and retour interpreting seem to cause some disruption. Regarding the three goals of interprofessional training – to give professional groups an opportunity to learn about, with and from each other – students of conference interpreting took the opportunity to learn with the political science group during the meeting, but appeared more reluctant to engage with them and learn from them duringperiods created for exchanges. In the concluding section, we suggest some remedies on how this learning could be maximised in future exercises.